Formulasi Strategi Pengembangan Kawasan UKM Berbasis Komoditas Unggulan di Kabupaten Indragiri Hilir Riau - . Novrizal (Telaah Bisnis, 2018)
Absract The purpose of this research is helping district Indragiri Hilir Riau Province to arrange appropriate development strategy for Micro, Small and Medium Enterprises (MSMEs) of banana chips. The district has superior commodity area of banana fruit, but it has not yet well managed. The information used in this research has been collected from interviews and observation. This research used SWOT-24K analysis to create development strategy of MSMEs of banana chips. The analysis has a function to highlight business position that can be used to create and formulate development strategy. Result of this research showed that appropriate strategy development for the current situation is the turnaround strategy by using government fund and conducting national banana chips event/program.